OPTIMISATION OF TREATMENT METHODS FOR NECROTIC FORMS OF ERYSIPELAS OF SOFT TISSUES - Korikhonov, D.N. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
This study aimed to improve the results of treatment of patients with complicated forms of erysipelas by solving several specific tasks: to study the state of immunological status in patients with complex forms of erysipelas; to study the efficacy of systemic enzyme therapy in the treatment of patients with complicated forms of erysipelas; to study the effectiveness of oxytocin in combination with therapeutic measures in patients with complex forms of erysipelas; to develop and introduce into clinical practice a surgical method of treatment using plasma technologies, early necrectomy with single-stage autodermoplasty in the complex treatment of complicated forms of erysipelas; to study the effectiveness of the clinical trial. Based on the studies carried out, we were the first in clinical practice to treat complicated forms of erysipelas by using a method that combines plasma technologies and early necrectomy with single-stage autodermoplasty. For the first time in the treatment of complex forms of erysipelas, oxytocin was used in combination with surgical treatment, the action of which is aimed at eliminating the infectious agent from the intracellular depot, and its effectiveness was proven. In combination with the measures taken, an antibacterial therapy regimen has been developed aimed at eliminating microorganisms from the area of the pathological process. As an additional treatment, in contrast to the previously proposed treatment regimens, a drug of systemic enzyme therapy - phlogenzyme - was used.